2013
DOI: 10.1371/journal.pone.0063826
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Global Gene Expression of Gastric Cardia and Noncardia Cancers from a High-Risk Population in China

Abstract: ObjectiveTo profile RNA expression in gastric cancer by anatomic subsites as an initial step in identifying molecular subtypes and providing targets for early detection and therapy.MethodsWe performed transcriptome analysis using the Affymetrix GeneChip U133A in gastric cardia adenocarcinomas (n = 62) and gastric noncardia adenocarcinomas (n = 72) and their matched normal tissues from patients in Shanxi Province, and validated selected dysregulated genes with additional RNA studies. Expression of dysregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 37 publications
4
82
0
Order By: Relevance
“…Differences could be identified for proximal versus distal gastric cancer of the intestinal type, especially when compared with diffuse-type neoplasias [150,151]. Lei et al [152] suggested a stratification into three different gastric cancer subtypes showing not only specific pathobiological characteristics but also remarkable differences concerning the response to treatment with either 5-fluorouracil or compounds targeting the PI3K-Akt-mTOR axis.…”
Section: Host-related Factorsmentioning
confidence: 99%
“…Differences could be identified for proximal versus distal gastric cancer of the intestinal type, especially when compared with diffuse-type neoplasias [150,151]. Lei et al [152] suggested a stratification into three different gastric cancer subtypes showing not only specific pathobiological characteristics but also remarkable differences concerning the response to treatment with either 5-fluorouracil or compounds targeting the PI3K-Akt-mTOR axis.…”
Section: Host-related Factorsmentioning
confidence: 99%
“…Two major types can be distinguished; the tumors located in the distal region (non-cardia cancer) and in the proximal region (cardia cancer) (McColl, 2006). These two anatomical subtypes are different in their etiology and epidemiology Derakhshan et al, 2008;Bertuccio et al, 2009;Wang et al, 2013). Some of the main differences between anatomical subtypes of GC have been addressed with more detail by previously published excellent reviews (McColl, 2006;Colquhoun et al, 2015;Huang, Sun, Fang, Zhou, & Zou, 2016).…”
Section: Histopathologymentioning
confidence: 99%
“…77 As of this writing, several basic science studies have been conducted for the molecular classification of gastric cancer in terms of prognostic factors, response to chemotherapy, distinct therapeutic targets, and diagnostic biomarkers. [78][79][80][81] However, most of these studies had a similar limitation of sample size or analyzing technique, and failed to show unique molecular characteristics that accounts for the epidemiologic or ethnic heterogeneity in clinical outcomes. Recently the Cancer Genome Atlas Research Network reported the comprehensive characterization of gastric cancer, which described the molecular evaluation of 295 primary gastric adenocarcinomas.…”
Section: Genetic Disparitymentioning
confidence: 99%